2015
DOI: 10.1016/j.jceh.2014.02.007
|View full text |Cite
|
Sign up to set email alerts
|

Management of Covert Hepatic Encephalopathy

Abstract: Hepatic encephalopathy is a reversible progressive neuropsychiatric disorder that encompasses a wide clinical spectrum. Covert hepatic encephalopathy is defined as patients with minimal hepatic encephalopathy and Grade I encephalopathy by West-Haven Criteria. Terminology such as "sub-clinical", "latent", and "minimal" appear to trivialize the disease and have been replaced by the term covert. The lack of clinical signs means that covert hepatic encephalopathy is rarely recognized or treated outside of clinical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 69 publications
0
14
0
1
Order By: Relevance
“…Historically, patients with post-TIPS HE were treated with a low-protein diet as well as nonabsorbable antibiotics and disaccharides to reduce intestinal neurotoxin production and absorption, which is increasingly being questioned today [11,12]. However, up to 8% of patients develop refractory HE after TIPS and there is only limited evidence about specific predictive risk factors for this purpose [13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Historically, patients with post-TIPS HE were treated with a low-protein diet as well as nonabsorbable antibiotics and disaccharides to reduce intestinal neurotoxin production and absorption, which is increasingly being questioned today [11,12]. However, up to 8% of patients develop refractory HE after TIPS and there is only limited evidence about specific predictive risk factors for this purpose [13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…5 Beneficial effects of LOLA for the management and treatment of HE have been reported in over 20 Randomized Clinical Trials (RCTs) in patients with cirrhosis. However, while recent reviews provide a consensus of opinion that LOLA is of benefit for the treatment of OHE, 6,7 evidence regarding its use in MHE has been questioned. 8,9 In the current AASLD-EASL Guidelines, recommendations relating to the use of LOLA for the treatment of HE in cirrhosis were based upon the results of a single RCT of intravenous LOLA while the oral formulation was deemed to be ineffective.…”
mentioning
confidence: 99%
“…There is a reduction in Veillonellaceae (gram negative cocci) and an increase in Eubacteriaceae (gram positive cocci). 40,41 Rifaximin is effective and well tolerated, with minimal systemic absorption. A meta-analysis comparing rifaximin with lactulose found that patients taking rifaximin fared better than those on lactulose.…”
Section: Correct Answers: C and Ementioning
confidence: 99%